Influence of the Concentration of Fe and Cu Nanoparticles on the Dynamics of the Size Distribution of Nanoparticles - Gudkov, Sergey V.; Baimler, Ilya V.; Uvarov, Oleg V.; Smirnova, Veronika V.; Volkov, Mikhail Yu; Semenova, Anastasia A.; Lisitsyn, Andrey B. (Frontiers in Physics, 2020)
The evolution of the size distribution of nanoparticles depending on the concentration of nanoparticles in a colloidal solution is investigated. The formation of new stable distributions shifted relative to the initial distribution is directly related to the processes of agglomeration of nanoparticles. Using successive two-fold dilutions of nanoparticles by 2-32 times, it was shown that the maximum of the nanoparticle size distribution shifts towards smaller sizes with a decrease in the concentration of nanoparticles, both for distributions by the number of nanoparticles and for distributions by mass of nanoparticles. Thus, with dilutions, the relative concentration of individual nanoparticles increases, while the number of particles in one aggregate decreases. A mathematical model has been created that predicts a change in distribution with a change in the concentration of nanoparticles in a colloid.